(untitled) (Scientific journal of the Fergana State University, 2024)
The article highlights the main conclusions formulated on the basis of studying the role of natural and geographical factors in the settlement of the population of Namangan, Ferghana and Andijan regions, which are regions of the Ferghana Valley. Based on the purpose of the study, the conclusions were developed separately for each landscape-altitude region of the Fergana Valley. At the same time, the possibilities of regional organization of individual landscape and high-altitude regions allocated for each administrative district from today’s point of view have been developed. The developed capabilities of the regional organization are finally summed up within the landscape-elevated region. Based on the purpose of this study, methods of systematic analysis, statistical evaluation, geoinformation systems were used, which are considered the most modern methods of geographical research.